2013
DOI: 10.1007/s10554-013-0230-x
|View full text |Cite
|
Sign up to set email alerts
|

Intra-procedural imaging of the left atrium and pulmonary veins with rotational angiography: a comparison of anatomy obtained by pre-procedural cardiac computed tomography and trans-thoracic echocardiography

Abstract: This study evaluated the feasibility and accuracy of three-dimensional rotational angiography (3DRA) to determine the anatomy of the left atrium (LA) and pulmonary veins (PVs) compared with cardiac computed tomography (CCT) and trans-thoracic echocardiography (TTE). One hundred two patients (56.1 ± 9.9 years, 86 males) with an indication for atrial fibrillation ablation were prospectively enrolled. Intra-procedural 3DRA was performed with power injected contrast medium (20 cc/s for 4 s, 240°) in the LA. 3DRA i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…17 Measurements of the LAA orifice diameters are increasingly essential to ensure the correct sizing and deployment of the occlusion device to optimize effectiveness and minimize complications. 18 The best imaging modalities for performing this measurement are cardiac computed tomography (CCT), 19 cardiac magnetic resonance (CMR), 20 and 3-D TEE, 21 which, as expected, provides more precise values than 2-D TEE. 22 It is worth mentioning that measuring LAA length and LAA ostium diameter by 2-D TEE 23 as demonstrated by the CUTE-CV study, in which a contrast agent was utilized.…”
Section: Left Atrial Closure Devicesmentioning
confidence: 67%
See 1 more Smart Citation
“…17 Measurements of the LAA orifice diameters are increasingly essential to ensure the correct sizing and deployment of the occlusion device to optimize effectiveness and minimize complications. 18 The best imaging modalities for performing this measurement are cardiac computed tomography (CCT), 19 cardiac magnetic resonance (CMR), 20 and 3-D TEE, 21 which, as expected, provides more precise values than 2-D TEE. 22 It is worth mentioning that measuring LAA length and LAA ostium diameter by 2-D TEE 23 as demonstrated by the CUTE-CV study, in which a contrast agent was utilized.…”
Section: Left Atrial Closure Devicesmentioning
confidence: 67%
“…Consequently, cardiac imaging has become of paramount importance for LAA anatomical characterization and device placement 17. Measurements of the LAA orifice diameters are increasingly essential to ensure the correct sizing and deployment of the occlusion device to optimize effectiveness and minimize complications 18. The best imaging modalities for performing this measurement are cardiac computed tomography (CCT),19 cardiac magnetic resonance (CMR),20 and 3-D TEE,21 which, as expected, provides more precise values than 2-D TEE 22.…”
Section: Left Atrial Closure Devicesmentioning
confidence: 99%
“…Cardiac imaging is of primary importance for LAA anatomical characterization, device size choice, ruling out LAA thrombus before the procedure, and minimizing complications. 27,28 Currently, the best preprocedural imaging modalities are cardiac computed tomography (CCT), 29 cardiac magnetic resonance, 30 and three-dimensional TEE. 31 Two-and three-dimensional TEE are commonly used during LAA closure procedure.…”
Section: Transcatheter Devices For Left Atrial Appendage Closurementioning
confidence: 99%
“…Park et al [3] investigated the feasibility and accuracy of 3D rotational angiography (3DRA) to determine the anatomy of the left atrium (LA) and pulmonary veins (PVs) compared with cardiac computed tomography (CCT) and trans-thoracic echocardiography (TTE) in a population of 102 patients. They concluded that this intra-procedural imaging resulted in 3DRA LA volumes (120 ± 32 mL) being greater than those found by CCT (109 ± 35 mL) or TTE (64 ± 23 mL), although with high correlations.…”
Section: Rotational Angiographymentioning
confidence: 99%